The effects of different dietary levels of betaine and methionine as attractant on the growth factors and survival rate of juvenile beluga (Huso huso) - Sudagar, M.; Azari Takami, Gh.; Panomarev, C.A.; Mahmoudzadeh, H.; Abedian, A.; Hosseini, S.A. (2005)
In an 8-week feeding trial, attractants betaine, methionine and a mixture of betaine and methionine were added to diet of juvenile beluga (1-huso huso) at different levels to assess their effects on growth and survival rate of the fish. In the trial, carried out in Shahid Marjani center for sturgeon hatchery and cultivation in Golestan Province of Iran, three different dietary levels 0.5%, 1% and 1.5% of attractants were used in PVC tanks filled with about 350 liters of water. We stocked 20 juvenile belugas with an average weight 28.2 ±2.63 grams in the tanks and fed them with four daily meals. Growth and survival factors were analyzed at the end of the trial period which showed that the addition of attractants in diets led to improvement of body weight gain, weight gain percentage* specific growth rate (SGR), protein efficiency ratio (PER), net protein utilization (NPU), condition factor(CF), survival, price index(PI) compared to control. The addition also led to a decrease in food conversion ratio (FCR) compared to control. The best improvement in indices was achieved with a diet enriched with 0.5% betaine and 1% methionine.